Mental Accounting Experiment: Mode of Payment Effect on Treating Money - Etik Kresnawati; Ahmad Bunyan Wahib; Ruspita Rani Pertiwi (Journal of Accounting and Investment, 2019)
This study examines the argument of mental accounting theory that individuals will behave differently in treating money. More specifically, this study empirically tests whether the difference in payment mode, cash and debit cards, will affect the amount of money spent by individuals when shopping and donation. The data were collected through a laboratory experimental design involving 76 female students from Muhammadiyah Boarding School and Pondok Pesantren Baitussalam Yogyakarta. Using MANOVA as the analysis tool, the results showed that the mode of payment did not affect the amount of money for shopping, but it affected the amount of donation. Subjects who used a debit card show an average number of donations that were larger compared to the subjects in the cash group. The results implied that debit card users, especially students, in this case, are not proven to behave more consumptively as predicted by the theory. While the positive impact is that debit cards can be a means for students to do more charity through donations. Thus, these results are in line with the objective of a cashless society program launched by Bank Indonesia. The important thing that should not be ignored in Less Cash Society programs at educational institutions is the policy of limiting the amount of money students can spend.